Identity and multigenerational persistence - Chinmayi Srikanth; Shubhasis Dey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The study aims at bridging gaps in both theoretical and empirical literature pertaining to multigenerational persistence. From a theoretical standpoint, it argues that parental altruism is influenced by social heterogeneity rather than income-based heterogeneity. One's position in the social hierarchy, therefore, determines the motive for altruism and is in turn observed in the persistence mechanism. The study finds that for India, persistence mechanisms for education are indeed different for various identity groups (caste and religion) depending on the region to which they belong. We also study what this means for reinforcement/disintegration of (dis)advantage for these groups. By finding evidence for the The Great Gatsby relation, the study contends that policymakers must target inequality rather than generational persistence. This study is also the first to develop an identification strategy that is unique to India-the abolition of untouchability in 1955, to account for endogeneity in the father's education.
Keywords: I24; J15; J62; 330; persistence; multigenerational mobility; identity; education; untouchability; India